1998
DOI: 10.1021/ef980006y
|View full text |Cite
|
Sign up to set email alerts
|

Copper Removal from Fuel by Solid-Supported Polyamine Chelating Agents

Abstract: The presence of copper in hydrocarbon fuels impairs fuel stability and jet-engine performance. We report here the results of an investigation on the feasibility of removing copper from hydrocarbon liquid using chelators attached to various support materials. The chelators, 1,4,8,-11-tetraazacyclotetradecane (cyclam) and N 1 -[3-(trimethoxysilyl)propyl]diethylenetriamine (DETA), were attached to polystyrene, agarose, or silica. Copper extraction from JP-5 and dodecane with the immobilized chelators, both cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Most studies involving silica-based materials covalently functionalized with cyclam derivatives have been performed by the groups of Guilard, ,, Corriu, and some others. , Materials were either silica gel bound cyclam (obtained by grafting or sol−gel synthesis) , , or cyclam-functionalized mesoporous solids (grafted or co-condensed with cyclam groups attached to the surface of mesochannels, or as periodic mesoporous organosilicas containing cyclam moieties in the mesopore walls). , ,, They have found applications mainly in catalysis, , chromatography, ,, or gas adsorption. ,, Metal-loaded hybrid materials incorporating metal cations such as Cu(II), Co(II), or Eu(III) have also been prepared and characterized. It was suggested that their coordination chemistry in the solid differs from that in solution. ,,, Metalation can be performed before synthesis of the hybrid (i.e., on the cyclam-functionalized alkoxysilane precursor) or afterward by allowing the materials to react with solutions containing the metal ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies involving silica-based materials covalently functionalized with cyclam derivatives have been performed by the groups of Guilard, ,, Corriu, and some others. , Materials were either silica gel bound cyclam (obtained by grafting or sol−gel synthesis) , , or cyclam-functionalized mesoporous solids (grafted or co-condensed with cyclam groups attached to the surface of mesochannels, or as periodic mesoporous organosilicas containing cyclam moieties in the mesopore walls). , ,, They have found applications mainly in catalysis, , chromatography, ,, or gas adsorption. ,, Metal-loaded hybrid materials incorporating metal cations such as Cu(II), Co(II), or Eu(III) have also been prepared and characterized. It was suggested that their coordination chemistry in the solid differs from that in solution. ,,, Metalation can be performed before synthesis of the hybrid (i.e., on the cyclam-functionalized alkoxysilane precursor) or afterward by allowing the materials to react with solutions containing the metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies involving silica-based materials covalently functionalized with cyclam derivatives have been performed by the groups of Guilard, 38,39,[43][44][45][46][47][48] Corriu, [46][47][48][49][50][51][52][53] and some others. 37,[54][55][56][57][58] Materials were either silica gel bound cyclam (obtained by grafting or sol-gel synthesis) [37][38][39][45][46][47][48][49][54][55][56][57] or cyclam-functionalized mesoporous solids (grafted or co-condensed with cyclam groups attached to the surface of mesochannels, or as periodic mesoporous organosilicas containing cyclam moieties in the mesopore walls). 43,[50][51][52][53]58,59 They have found applications mainly in catalysis, 58,59 chromatography, 54,55,57 or gas adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…The first method is usually costly and not always effective. The second method has been the subject of recent investigations, , but overall economic viability in full-scale commercial and military applications has yet to be clearly demonstrated. The last method is the one usually chosen, and is accomplished by using additives known as copper (or metal) deactivators that form complexes with the copper, rendering it catalytically inactive.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies involving silica functionalised with macrocycles, such as cyclen and cyclam (Figure 4.2), were conducted by Guilard 123,[235][236][237][238][239][240][241] and Corriu 235,237,239,240,[242][243][244][245] , but a number of others [246][247][248][249][250][251] have contributed to the literature as well. These materials are mainly used for gas adsorption, catalysis, or chromatography.…”
Section: Incorporation Of Cu(ii)-ligand Complexesmentioning
confidence: 99%
“…At times, assumptions are made about the product without satisfactory final characterisation, and, in multiple cases, characterisation data of the modified silica are incomplete or absent. For instance, Puranik et al 248 and Bagnoud et al 255 infer the generation of the desired product from its ability to retain Cu(II), rather than from direct measurements and characterisation of the modified silica. For those studies in which data are reported, common characterisation techniques of the silica include FT-IR spectroscopy, CHN elemental analysis, microscopy, solid-state cross-polarisation magic angle spinning nuclear magnetic resonance spectroscopy (CP-MAS NMR), and Brunauer, Emmett, and Teller (BET) surface area measurements.…”
Section: Incorporation Of Cu(ii)-ligand Complexesmentioning
confidence: 99%